PENGARUH LATIHAN ABDOMINAL TERHADAP KEMAMPUAN HEADING PEMAIN SEPAK BOLA U 19-21 GUNUNG MEDAN DHARMASARAYA - Muhammad Rizki; Zuhar Ricky; Maldin Ahmad Burhan (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2022)
This research was motivated by the lack of good heading skills of U 19-21 soccer players in gunung Medan, Dharmasaraya. Efforts to overcome these problems require abdominal exercises. This study aims to determine whether abdominal exercise has an effect on the heading ability of dharmasaraya mountain soccer players. This research is a type of quantitative research using an experimental method approach. While the form of research design used is